Tickner, Arlene B.; Smith, Karen (editors) International Relations from the Global South: Worlds of Difference. Abingdon, Oxon; New York, NY: Routledge, Series: Wording beyond the West, 2020, 1st edition, 368p. ISBN: 97811387990997 (hardback); 9781138799103 (paperback); 9781315756233 (ebook). - Araújo de Jesus, Raquel (Mural Internacional, 2021)
O presente texto tem como objetivo celebrar o lançamento do livro “International Relations from the Global South: Worlds of Difference” organizado por Arlene Tickner em parceria com Karen Smith. A proposta central do livro é ser um textbook, destinado aos alunos e professores de Relações Internacionais, que não apenas denuncia o paroquialismo do campo, mas que também lança luz para alternativas e novas abordagens construídas desde o Sul Global plural. Palavras-chave: Relações Internacionais; Sul Global; Novas abordagens. ABSTRACT This text aims to celebrate the launch of the book “International Relations from the Global South: Worlds of Difference” organized by Arlene Tickner in partnership with Karen Smith. The central purpose of the book is to be a textbook for students and teachers of International Relations, which not only denounces the parochialism of the field, but also sheds light on alternatives and new approaches built from the plural Global South. Keywords: International Relations; Global South; New approaches. Recebido em: 06 out. 2020 | Aceito em: 20 jan. 2021.